High-strength composites based on tung oil polyurethane and wood flour: Effect of the filler concentration on the mechanical properties - Casado, Ulises Martín (2009)
New composite materials with a high percentage of their composition based on renewable resources, matrix and reinforcement, were prepared. The excellent compatibility of the main phases lead to an unusual outstanding composite behavior as follows: higher modulus and strength, but also higher deformability and fracture resistance than the neat polymer. A bio-based polyol was obtained by chemical modification of tung oil to be used in the production of polyurethane composites reinforced with pine wood flour (WF). The mechanical behavior as a function of wood flour content was evaluated through tensile and impact tests. Increasing the filler content induced an increase in tensile modulus and strength as well as in impact strength. Composites containing 10 and 15 wt% of wood flour presented higher tensile ultimate strain than that of the unfilled polyurethane. These results were explained by a strong interfacial adhesion (physical and chemical bonding), which was also supported by SEM micrography and strength modeling